Is there hope for the expectations hypothesis? - Richard K. Crump; Stefano Eusepi; Emanuel Mönch (Federal Reserve Bank of New York, 2024)
Most macroeconomic models impose a tight link between expected future short rates and the term structure of interest rates via the expectations hypothesis (EH). While the EH has been systematically rejected in the data, existing work evaluating the EH generally assumes either full-information rational expectations or stationarity of beliefs, or both. As such, these analyses are ill-equipped to refute the EH when these assumptions fail to hold, fueling hopes for a "resurrection" of the EH. We introduce a model of expectations formation which features time-varying means and accommodates deviations from rationality. This model tightly matches the entire joint term structure of expectations for output growth, inflation, and the short-term interest rate from all surveys of professional forecasters in the U.S. We show that deviations from rationality and drifting long-run beliefs consistent with observed measures of expectations, while sizable, do not come close to bridging the gap between the term structure of expectations and the term structure of interest rates. Not only is the EH decisively rejected in the data, but model-implied short-rate expectations generally display, at best, only a weak co-movement with the forward rates of corresponding maturities.
Keywords: D84; E43; G12; 330; expectations formation; survey forecasts; expectations hypothesis